Efektivitas Program Tanda Tangan Elektronik di Diskominfosanditik Kabupaten Sumedang - Deden Haria Garmana; Afif Sugihartiawan; Neni Nuraeni; Rosa Adinda Rahayu; Sri Megayani; Yuyun Yulaeha; Torik Aziz (JRPA - Journal of Regional Public Administration, 2022)
Electronic signature is a signature that consists of electronic information that is attached, isolated or related to other electronic information that is used as a means of verification and authentication. With this program, access to services becomes more effective and efficient. This program supports the transformation of agencies to synergize better in the industrial era because everything can be done through technology with e-office applications as a support. The e-office application itself is an office application and can replace the management process that was previously done manually to a digital-based management system (Internet). This study aims to identify, analyze and obtain objective data and information regarding the Effectiveness of the Electronic Signature Program at the Informatics Communications and Statistics Agency (Diskominfosanditik) Sumedang Regency. To measure the extent to which a program is running, it can be seen from whether or not the objectives of the program have been achieved. This effort or method is called program effectiveness. The method used in this research process is a qualitative research method with data collection, observation steps, in-depth interviews and documentation. Data analysis techniques in this study are data reduction, data presentation and conclusions with data validation techniques carried out through data triangulation. The results of the study show that the effectiveness of the implementation of the Electronic Signature Program at the Office of Communication and Informatics, Encoding and Statistics (Diskominfosanditik) of Sumedang Regency has been quite effective in accordance with the plan, especially in targeting the right target, achieving program goals, evaluating and monitoring program implementation. However, in terms of program socialization, it is still not optimal, there is a lack of participation from the village government in terms of attendance at the implementation of the socialization. It is hoped that in the future the Government of the Office of Communication, Informatics, Encoding and Statistics will optimize the program from all aspects in order to achieve more effective and efficient services.